Electronic model with intelligent interface for interactive web-based intelligent tutoring system - Siraj, Fadzilah; Wan Ishak, Wan Hussain; Siraj, Saerah (2000)
The World Wide Web and the related Internet resources have become an increasing viable component in higher education pedagogy. This has lead to signijicant interest in an implementation web based education. However most of the courses available on the web are static hypertexts that do not promote interactive teaching and learning. Some of the courses have been developed as Intelligent Tutoring Systems that are suitable, as standalone applications. Few Intelligent Tutoring Systems have been implemented as web-based Intelligent Tutoring Systems. A study of the past and current trends of webbased courses reveals that it is vital to provide an interface in such a way that interaction between students, instructors and course contents are guaranteed. This paper proposed an intelligent interface suitable for web-based education, particularly to support webbased Intelligent Tutoring Systems. Such an interface will be incorporated in the electronic model so that the interface acts as the communication control between users and Intelligent Tutoring Systems.